Library survival and the economics of social change [soundrecording] - Downs, Anthony (Development Digest premier series, 1973)
Discusses from the sociologist's and economist's viewpoints, the background factors of our present social change, characteristics and functions of our libraries, specific challenges for librarians due to social change, and the meaning of all these factors.